The Influence Of Work Motivation, Communication Style, And Work Stress On The Work Environment Of Ppll At The Office Of Transportation Service, West Jakarta Administrative City - Fernandus David Prasetyo; Velly Randyantini (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
The purpose of this study was to determine work motivation, communication style and work stress on the work environment in PPLL at the West Jakarta Administration City Transportation Office. The population of this study included all traffic handling officers at the West Jakarta Administration City Transportation Agency. The analytical method used is data analysis in this study using SEM analysis in the SmartPLS application.